DESCRIPTION OF THE CLAIMS FILED AGAINST KINESIOLOGISTS REGISTERED WITH THE COLLEGE OF KINESIOLOGISTS OF CHILE A. G. (Cuestiones de Fisioterapia, 2007)
This study seeks to describe the claims interposed against of collegiate physical therapists to the Colegio de Kinesiologos de Chile A.G. since the creation of this Institution to year 2004.In August 2005, a new Law was promulgated, which establishes that Professional Schools «will have the faculty to know the claims that have been interposed about the ethical behavior of its members*. It is necessary, therefore, that Schools check and update its Ethical and Research Procedure Codes according to the changes in society that have been happening since the first Ethical Codes to these days. Information for this study was obtained from Colegio de Kinesiologos de Chile A.G. A total of 53 cases were analyzed.To collect the data were utilized distribution measures as frequency and percentages. To analyze the data were utilized the statistical mode and it was calculated the rate. As conclusion it was observed that the complainants are mainly from male gender and claims are concentrated in Metropolitan Region. The accused are mostly men. The physical therapists with less than 5 years of qualification fall in behaviors related with «Treatment from the Physical Therapist» and «Therapeutic Procedures the Physical Therapists with more than 31 years of qualification show the major frequency of claims in the «Conflicts among health's professionals)) category. The claims distribution by categories was: «Conflicts among health's professionals)) with a 39.59 %, «Treatment from the Physical Therapist)) and «Therapeutic Procedure)) with a 33.92 %; «Administrative-Financial» and ((Misleading Advertising)) with a 22.72 %, y «More than a subcategory» with a 3.77 %. Around two thirds of the claims show incomplete record. The most common sanction corresponds to «censure in writing».